2016
DOI: 10.1128/genomea.01261-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Marinitoga camini Isolates Producing Bacterioviruses

Abstract: Here, we present the draft genome sequences of two thermophilic Marinitoga strain members of the Thermotogales order, Marinitoga camini DV1155 and Marinitoga camini DV1197. These strains were isolated from deep-sea hydrothermal vents of the Mid-Atlantic Ridge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Here, we report on the functional and genomic analysis of two new bacterioviruses that infect bacteria from the Marinitoga genus. Marinitoga camini virus 1 (MCV1) and Marinitoga camini virus 2 (MCV2) are siphoviruses that infect Marinitoga camini DV1197 and Marinitoga camini DV1155 respectively (Mercier et al, 2016). These bacteria are thermophiles and were isolated from deep-sea hydrothermal vents in the Mid-Atlantic Ridge.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report on the functional and genomic analysis of two new bacterioviruses that infect bacteria from the Marinitoga genus. Marinitoga camini virus 1 (MCV1) and Marinitoga camini virus 2 (MCV2) are siphoviruses that infect Marinitoga camini DV1197 and Marinitoga camini DV1155 respectively (Mercier et al, 2016). These bacteria are thermophiles and were isolated from deep-sea hydrothermal vents in the Mid-Atlantic Ridge.…”
Section: Introductionmentioning
confidence: 99%
“…values between strain BP5-C20A T genome and other related Marinitoga species for which genome data were available: M. lauensis LG1 T [44], M. camini str. 1197 [45], M. camini str.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…After extraction using a modified version of the method of Miller Table 1. Digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) values between the strain BP5-C20A T genome and other related Marinitoga species for which genome data were available: M. lauensis LG1 T [46], M. litoralis DSM 21709 T , M. hydrogenitolerans DSM 16785 T , M. camini strain 1197 [47], M. camini strain 1155 [47], Marinitoga sp. 1137, M. piezophila KA3 T [48].…”
Section: Fatty Acid Analysesmentioning
confidence: 99%
“…1137. All five proviral sequences encode for a LexA type transcriptional repressor, which has been suggested to function in viral cycle control[19]. The five sequences also contain multiple transcriptional regulators with XRE domains, and they share several hypothetical protein genes with no putative function assigned.It was demonstrated that the MPV1 virions of M. piezophila not only carry the viral DNA but preferentially package a plasmid of 13.3 kb (pMP1) also carried in M. piezophila.…”
mentioning
confidence: 99%